Validation of the Fear and Avoidance of Memory Loss scale in community‐based older adults - Francesca R. Farina; Pavithra Pavithra; Hosanna An; Melissa Marquez; Patricia O'Loughlin; John Regan; Michelle Taddeo; Marc Bennett; Bert Lenaert; James W. Griffith (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2023)
Abstract Introduction Alzheimer's disease and related dementias (ADRD) are among the most feared conditions. However, research around ADRD‐specific fear and avoidance behaviors is lacking. Here, we validated a novel measure of fear and avoidance specific to memory loss, the Fear and Avoidance of Memory Loss (FAM) scale, and examined associations between fear avoidance and psychosocial functioning in older adults. Methods We assessed FAM Scale internal reliability and concurrent validity, and candidate subscales across two samples (total N = 813). We then examined associations between fear avoidance and memory performance, anxiety, depressive symptoms, sleep, social functioning, and quality of life. Results We identified two subscales: fear and avoidance, which yielded strong psychometric validity. Higher fear was associated with memory failures and sleep disturbance. Higher avoidance was associated with memory failures, poorer verbal memory, reduced social functioning, and quality of life. Discussion We present the first measure of fear avoidance specific to memory loss. We propose that targeting fear avoidance can promote ADRD risk reduction and resiliency.